p57kip2 regulates glial fate decision in adult neural stem cells - Jadasz, Janusz Joachim; Rivera, Francisco J.; Taubert, Agnes; Kandasamy, Mahesh; Sandner, Beatrice; Weidner, Norbert; Aktaş, Orhan; Hartung, Hans-Peter; Aigner, Ludwig; Küry, Patrick (Development, 2012)
Our recent studies revealed p57kip2 as an intrinsic regulator of late gliogenesis and demonstrated that in oligodendroglial precursor cells p57kip2 inhibition leads to accelerated maturation. Adult neural stem cells have been described as a source of glial progenitors; however, the underlying mechanisms of cell fate specification are still poorly understood. Here, we have investigated whether p57kip2 can influence early events of glial determination and differentiation. We found that Sox2/GFAP double-positive cells express p57kip2 in stem cell niches of the adult brain. Short-hairpin RNA-mediated suppression of p57kip2 in cultured adult neural stem cells was found to strongly reduce astroglial characteristics, while oligodendroglial precursor features were increased. Importantly, this anti-astrogenic effect of p57kip2 suppression dominated the bone morphogenetic protein-mediated promotion of astroglial differentiation. Moreover, we observed that in p57kip2 knockdown cells, the BMP antagonist chordin was induced. Finally, when p57kip2-suppressed stem cells were transplanted into the adult spinal cord, fewer GFAP-positive cells were generated and oligodendroglial markers were induced when compared with control cells, demonstrating an effect of in vivo relevance.